Ekphrastic encounters : New interdisciplinary essays on literature and the visual arts - Meek, Richard, 1975-; Kennedy, David, 1959- (Book collections on Project MUSE., 2019)
This book offers a comprehensive reassessment of ekphrasis: the verbal representation of visual art. Ekphrasis has been traditionally regarded as a form of paragone (competition) between word and image. This interdisciplinary collection of essays seeks to complicate this critical paradigm and proposes a more reciprocal model of ekphrasis that involves an encounter or exchange between visual and textual cultures. 0This critical and theoretical shift demands a new form of ekphrastic poetics, which is less concerned with representational and institutional struggles, and more concerned with ideas of ethics, affect and intersubjectivity. Ekphrastic encounters brings together leading scholars working in the field of word-and-image studies and offers a fresh exploration of ekphrastic texts from the Renaissance to the present day. Taken together, the chapters establish a new set of theoretical frameworks for exploring the ekphrastic encounter.